Feud, Law, and Society in Mid-Nineteenth-Century Northern Albania. - Bayraktar, Uğur (Welt des Islams, 2023)
The present article investigates the kanun or Albanian "customary law", with a particular focus on feuds in the town of Dibra. It explores a case of Ottoman legal pluralism in which the kanun and Ottoman law interacted, a major watershed in the development of Ottoman law. By shifting the perspective to the Albanian highlanders' understanding of "law", this paper sheds light on how a set of customary laws contributed to the making of the Tanzimat , which called for a standardised legal framework in the provinces. It examines the means the Ottoman government developed to eliminate feuds and demonstrates that the Tanzimat converged with the principles of Albanian customary law. Analysis of this interaction between the kanun and state law demonstrates how this process constituted one of the foundations of the modern Ottoman legal order in northern Albania.